Brominated Thiophenes as Precursors in the Preparation of Brominated and Arylated Anthraquinones - Thies Thiemann; Jesus Iniesta; Yasuko Tanaka (Molecules, 2009)
Brominated anthraquinones can be synthesized directly from bromothiophenes when these are reacted with 1,4-naphthoquinones in the presence of meta-chloroperoxybenzoic acid. The bromoanthraquinones are versatile building blocks in the preparation of arylated anthraquinones and of extended π-systems with interspersed anthraquinone units.